1982
DOI: 10.1037/0022-006x.50.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Chronological age differences in MMPI scores of male chronic alcoholics seeking treatment.

Abstract: Gynther's general hypothesis that older subjects self-report better adjustment on the Minnesota Multiphasic Personality Inventory than do younger subjects was tested among 616 male chronic alcoholics classified into five age groups: 30 or younger, 31-40, 41-50, 51-60, and 61 or older. Multivariate and univariate analyses of variance and covariance supported Gynther's general hypothesis as well as three specific corollary hypotheses predicting that older alcoholics, relative to younger alcoholics, are lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Across diagnostic categories and racial groups, age was positively correlated with depression and somatic concerns and inversely related to antisocial personality traits. These differences on the MMPI are generally consistent with previously reported age differences among alcoholics and within the general psychiatric population (Aaronson, 1958; Delatte & Delatte, 1984; Faulstich et al, 1985; Filstead et al, 1983; Graham & Strenger, 1988; Gynther & Shimkunas, 1966; McGinnis & Ryan, 1965; McLachlan, 1975; Penk, Charles et al, 1982; Schenkenberg et al, 1984; Wilson et al, 1977). Thus, age effects on MMPI do not appear to interact with race or type of substance abused.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Across diagnostic categories and racial groups, age was positively correlated with depression and somatic concerns and inversely related to antisocial personality traits. These differences on the MMPI are generally consistent with previously reported age differences among alcoholics and within the general psychiatric population (Aaronson, 1958; Delatte & Delatte, 1984; Faulstich et al, 1985; Filstead et al, 1983; Graham & Strenger, 1988; Gynther & Shimkunas, 1966; McGinnis & Ryan, 1965; McLachlan, 1975; Penk, Charles et al, 1982; Schenkenberg et al, 1984; Wilson et al, 1977). Thus, age effects on MMPI do not appear to interact with race or type of substance abused.…”
Section: Discussionsupporting
confidence: 90%
“…Alcoholics in treatment typically are older than drug abusers in treatment (Keskinen, 1987; cf. Method section), and age is known to be correlated with MMPI scores in both the general psychiatric population (e.g., Aaronson, 1958; Gynther & Shimkunas, 1966; Schenkenberg, Gottfredson, & Christensen, 1984) and among alcoholics (Delatte & Delatte, 1984; Faulstich, Carey, Delatte, & Delatte, 1985; Filstead, Drachman, Rossi, & Getsinger, 1983; Graham & Strenger, 1988; McGinnis & Ryan, 1965; McLachlan, 1975; Penk, Charles, et al, 1982; Wilson, Mabry, Khavari, & Dalpes, 1977). In both the general psychiatric population and among alcoholics, MMPI scales Hypochondriasis ( Hs ) and Depression ( D ) are usually higher in older subjects and scales F , Psychopathic Deviate ( Pd ), Psychasthenia ( Pt ), Schizophrenia ( Sc ), and Hypomania ( Ma ) are usually lower in older subjects.…”
mentioning
confidence: 99%
“…Both younger and older alcoholics tend to produce elevated Scale 4 scores (MacAndrew, 1978), but most investigators have reported that the Scale 4 scores of older alcoholics are not as elevated as those of younger alcoholics (Delatte, 1984; Faulstich, Carey, Delatte, & Delatte, 1985; McGinnis & Ryan, 1965; Penk, Charles, Patterson, Roberts, Dolan, & Brown, 1982). The relation between the Scale 4 scores of alcoholics and age has been interpreted to indicate that older alcoholics have less severe problems with impulsivity than younger alcoholics (Penk et al, 1982). However, the relation between age and Scale 4 scores is a general finding and is not unique to alcoholic subjects.…”
Section: Research Based On Standard Mmpi Scales: Scale 4 Elevationsmentioning
confidence: 99%